Climate-Driven Range Shifts of Brown Seaweed Sargassum horneri in the Northwest Pacific - Li, Jing-Jing; Huang, Sheng-Hui; Liu, Zheng-Yi; Bi, Yuan-Xin (Frontiers in Marine Science, 2020)
Climate-driven shifts of coastal species’ ranges constitute a key factor shaping both the vegetation composition and biodiversity of coastal ecosystems. Although phylogeographic studies relying on genetic data have shed light on the evolutionary history of macroalgae along the Northwest Pacific (NW-Pacific) coast, their distribution dynamics are less understood and require interdisciplinary examination. Here, we used a combination of species distribution models (SDMs) and genetic data to explain the causes of population persistence and genetic differentiation and their consequences for the brown seaweed Sargassum horneri in the NW-Pacific. In this region, the phylogeographic structure of S. horneri was analyzed by screening 72 populations spawning across the entire coastal distribution and obtaining their mtDNA cox3 data. Population genetic structure and SDMs based on paleoclimatic data consistently revealed that southern coasts of the Sea of Japan, North-Pacific-Japan, and the northern part of Okinawa Trough might have served as potential refugia for S. horneri during the Last Glacial Maximum (LGM). Furthermore, we projected the distribution dynamics of S. horneri under future climate scenarios. The range of S. horneri was predicted to move northward, with a significant loss of suitable habitat, under the high emissions scenario (RCP 8.5). By contrast, projected range shifts were minimal under the low emissions scenario (RCP 2.6). Furthermore, North-Pacific-Japan was projected to be long-term persistence habitat for S. horneri under future climatic conditions, thus including this area in conservation planning could help mitigate for climate change implications. Our results enable a better understanding of the impacts of climate change on the spatio-temporal distribution of macroalgae and how this can inform coastal management and marine conservation planning.